Complex ceramic architectures by directed assembly of 'responsive' particles. Issue 1 (January 2017) - García-Tuñón, Esther; Machado, Gil C.; Schneider, Marc; Barg, Suelen; Bell, Robert V.; Saiz, Eduardo
Abstract: Surface functionalization of alumina powders with a responsive surfactant (BCS) leads to particles that react to a chemical switch. These 'responsive' building blocks are capable of assembling into macroscopic and complex ceramic structures. The aggregation follows a bottom up approach and can be easily controlled. The directed assembly of concentrated suspensions leads to highly dense (∼99%) ceramic components with average 4-point bending strength of ∼200 MPa. On the other hand, the emulsification of suspensions with concentrations from 7 to 43 vol% and 50 vol% decane results in emulsions with different properties (stability, droplet size and distribution). The oil droplets provide a soft template confining the alumina particles in the continuous phase and at the oil/water interfaces. Aggregation of these emulsions followed by drying and sintering leads to macroporous (pore sizes ranging from 30 to 4 μm) alumina structures with complex shapes and a wide range of microstructures, from closed cell structures to highly interconnected foams with total porosities up to 83%. Alumina scaffolds with ∼55% porosity can reach crushing strength values above 300 MPa in compression and ∼50 MPa in 4-point bending.